2016
DOI: 10.1016/j.ijhydene.2016.07.036
|View full text |Cite|
|
Sign up to set email alerts
|

Transport properties of acceptor-doped barium zirconate by electromotive force measurements

Abstract: In this work, a systematic work was performed to investigate the electrochemical transport properties of acceptor-doped BaZrO3 by measuring electromotive force on various gas concentration cells. For the measurements in the wet oxidizing atmosphere, where significant hole conduction occurs, the transport numbers of the ionic conduction in the oxidizing atmosphere were corrected by taking the effect of electrode polarization into consideration. The results revealed that regardless of whether Sc, Y, In, Ho, Er, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 46 publications
0
72
1
Order By: Relevance
“…And conventionally, the transport number of ionic conduction ( t ion ) can also be estimated by simulating the dependence of conductivity on partial pressure of oxygen (pnormalO2). Roughly speaking, t ion is derivable from the conductivity in wet O 2 and wet H 2 by assuming that only the hole conductivity is a function of pnormalO2, but the ionic conductivity keeps invariable . However, the transport numbers determined by the EMF method deviate greatly from those determined from the conductivity measurement in this work.…”
Section: Discussionmentioning
confidence: 78%
“…And conventionally, the transport number of ionic conduction ( t ion ) can also be estimated by simulating the dependence of conductivity on partial pressure of oxygen (pnormalO2). Roughly speaking, t ion is derivable from the conductivity in wet O 2 and wet H 2 by assuming that only the hole conductivity is a function of pnormalO2, but the ionic conductivity keeps invariable . However, the transport numbers determined by the EMF method deviate greatly from those determined from the conductivity measurement in this work.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study from our group reported that BaZr 0.9 Y 0.1 O 3‐δ exhibited t ion around 0.24 at 700°C in wet oxygen (pH20 = 0.05 atm). At the same temperature, interestingly, Bao, et al reported t ion of CaZr 0.95 Y 0.05 O 3‐δ close to unity, and Pérez‐Coll, et al reported t ion of SrZr 0.9 Y 0.1 O 3‐δ higher than 0.8 in wet oxidizing atmosphere, indicating the possibility to increase t ion of BZY by substituting Ba partially with Sr or Ca.…”
Section: Introductionmentioning
confidence: 86%
“…Referring to the candidate for electrolytes of PCFCs, Y‐doped BaZrO 3 (BZY), especially BaZr 0.8 Y 0.2 O 3‐δ (BZY20), is currently regarded as the most promising one, as it shows high proton conductivity in wet atmosphere and significant chemical stability against CO 2 . Although the ionic (mainly protonic) transport number ( t ion ) of BZY is almost unity in wet reducing atmosphere, it deviates obviously from unity by exposing to wet oxidizing atmosphere at the temperature higher than 500°C, due to the generation of hole conduction . As the hole conduction results in the formation of leakage current in the electrolyte during the operation, and thereby reduces the performance of PCFCs, it's extremely important to suppress the hole conduction in the wet oxidizing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The voltages measured in the hydrogen concentrationc ells were very close to the Nernst voltage, indicating that regardless of the NiO, CuO, or ZnO additive, almost pure ionic conduction (protons and oxide ions) occurred (Figure S16). [8,44] As shown in Figure 10, regardlesso fw hether NiO, CuO, or ZnO was added into BZY20,a lmost pure ionic conduction, mainlyp rotonc onduction, occurred in ah ydrogen atmosphere. Here, compensation was performed in a wet oxidizing atmosphere by taking the electrodep olarization effect into consideration.…”
Section: Transport Numbersmentioning
confidence: 99%
“…[8,43] The transport numbers evaluated in the oxygen atmosphere were compensated by taking the effect of the electrode polarization into consideration. Pt plates wrapped in silver mesh were used as ac urrent collector.P tw ire was used to lead the current to af requency response analyzer (Solartron SI 1260, Solartron Analytical, Farnborough, UK).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%